Downmodulation of key inflammatory cell markers with a topical Janus kinase 1/2 inhibitor. (14th October 2015) - Punwani, N.; Burn, T.; Scherle, P.; Flores, R.; Shi, J.; Collier, P.; Hertel, D.; Haley, P.; Lo, Y.; Waeltz, P.; Rodgers, J.; Shepard, S.; et al.
Summary: Background: INCB018424 is a novel, potent Janus kinase (JAK)1/JAK2 inhibitor that blocks signal transduction of multiple proinflammatory cytokines. Objectives: To evaluate the safety, tolerability, pharmacokinetics, pharmacodynamics and preliminary efficacy of topical INCB018424 phosphate cream in patients with plaque psoriasis. Methods: Topical INCB018424 phosphate 1·0% or 1·5% cream was applied once daily (QD) or twice daily (BID) for 4 weeks to 2–20% body surface area in five sequential cohorts of five patients aged 18–65 years. Target lesions were scored on a scale of 0–4 for erythema, scaling and thickness. Additionally, the overall disease activity in each patient was measured using Physician's Global Assessment. INCB018424 concentrations were measured in plasma, and cytokine stimulated phosphorylated signal transducer and activator of transcription 3 phosphorylation (pSTAT3) levels in peripheral blood cells were evaluated. Pretreatment and post‐treatment skin biopsies were compared with healthy skin, including evaluation of histopathology, immunohistochemistry and mRNA expression. Results: Treatment with INCB018424 phosphate cream either 1·0% QD or 1·5% BID resulted in improvements in lesion scores. No significant inhibition of pSTAT3 in peripheral blood cells was observed following topical application, consistent with the generally low steady‐state plasma concentrations of INCB018424 measured. Transcriptional markers of immune cell lineage/activation in lesional skin were reduced by topical INCB018424, with correlations observed between clinical improvement and decreases in markers of T helper 17 lymphocyte activation, dendritic‐cell activation and epidermal hyperplasia. INCB018424 treatment reduced epidermal hyperplasia and dermal inflammation in most patient samples, with reductions in CD3, CD11c, Ki67 and keratin 16 observed by immunohistochemical analysis. Conclusions: Topical INCB018424 dosed for 28 days QD or BID is pharmacologically active in patients with active psoriasis and modulates proinflammatory cytokines in the pathogenesis of psoriatic lesions. Abstract : What's already known about this topic? Cytokines are implicated in the pathogenesis of psoriasis, and Janus kinase (JAK) inhibitors have efficacy in psoriasis. Many of the cytokines implicated in the pathogenesis of psoriasis signal via the JAK–signal transducer and activator of transcription (STAT) pathway. What does this study add? This study showed that the topical JAK1/JAK2 inhibitor INCB018424 is pharmacologically active in patients with active psoriasis, modulates proinflammatory cytokines, and is well tolerated. JAK–STAT inhibition with INCB018424 cream may represent a new treatment option in psoriasis.